1999
DOI: 10.1007/s004410051323
|View full text |Cite
|
Sign up to set email alerts
|

Development of the wing discs of Zophobas atratus under natural and experimental conditions: occurrence of a gradual larval-pupal commitment in the epidermis of tenebrionid beetles

Abstract: Using light and electron microscopy, we studied the development of the wing discs in the large beetle Zophobas atratus, under natural and experimental conditions. A reversible differentiation of the wing discs is usually observed during supernumerary instars of crowded larvae. Juvenile hormone analog (JHA) application during the wandering period or compelled experimental crowding during the larval-pupal switchover - or commitment - inhibits the onset of metamorphosis. Isolation, followed by recrowding, also in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 36 publications
2
7
0
Order By: Relevance
“…The expression of these isoforms during the prepupal period appears to correspond to the time when the ecdysteroid titer rises prior to pupation in Tribolium and Tenebrio molitor (Hirashima et al, 1995;Quennedey and Quennedey, 1999). As in Bombyx penultimate stage larvae (Ijiro et al, 2004;Nishita and Takiya, 2004), low levels of br are present earlier in Tribolium larvae, and even the embryos (Konopova and Jindra, 2008), but no disruption of larval development has been noted after br dsRNA treatment in the penultimate (our study) or earlier (Konopova and Jindra, 2008) stages.…”
Section: Evolution Of Brsupporting
confidence: 45%
See 1 more Smart Citation
“…The expression of these isoforms during the prepupal period appears to correspond to the time when the ecdysteroid titer rises prior to pupation in Tribolium and Tenebrio molitor (Hirashima et al, 1995;Quennedey and Quennedey, 1999). As in Bombyx penultimate stage larvae (Ijiro et al, 2004;Nishita and Takiya, 2004), low levels of br are present earlier in Tribolium larvae, and even the embryos (Konopova and Jindra, 2008), but no disruption of larval development has been noted after br dsRNA treatment in the penultimate (our study) or earlier (Konopova and Jindra, 2008) stages.…”
Section: Evolution Of Brsupporting
confidence: 45%
“…3A), and the expression remained high for the remainder of the instar. This rise in expression occurs around 1 to 2 days before the larvae enter the stationary crooked posture stage that signals the onset of visible metamorphosis (Quennedey and Quennedey, 1999). It should be noted that different numbers of cycles were used for each isoform, and, based on the number of cycles alone, br-Z4 mRNA appears to be most abundantly expressed, whereas br-Z2 mRNA is expressed least abundantly.…”
Section: Expression Of Br Isoforms In Normal and Jhtreated Larvaementioning
confidence: 99%
“…So-called "regressive molts," at which wing buds are reduced or lost, are a common occurrence in Kalotermitidae (Grassé and Noirot, 1947;Roisin, 1990) and some Rhinotermitidae (Miller, 1942;Buchli, 1958), but up to now such molts were never shown to constitute an obligatory event in any individual's ontogeny. An analogous phenomenon, involving a reversion of the differentiation of wing disc cells, has also been observed in tenebrionid beetles under particular conditions of crowding or experimental treatment by JH analogs (Quennedey and Quennedey, 1999).…”
Section: Discussion Caste Morphology and Developmentmentioning
confidence: 91%
“…Both studies have shown that loss of sensitivity of wing discs and epidermal cells to JH completes the commitment process. Application of JHA during the final instar of tenebrionid beetles revealed the commitment period for wings, antennae, eyes, prothorax and tarsi (Connat et al, 1984;Quennedey and Quennedey, 1999). Though we could not directly relate because of the difference in developmental period of T. castaneum, the commitment period is likely to occur through the end of the feeding stage (Parthasarathy and Palli, unpublished).…”
Section: 2mentioning
confidence: 85%